Divergensi Mazhab Nahwu: Kajian Komparatif Aliran Basrah-Kufah - Rabiul Farra Tazkiyatun (Universitas 45 Surabaya, 2024)
This research involves an expression of the mazhab of Nahwu Basrah and Kufah in the causes and consequences of divergence of perspective. The factors that led to the birth of the knowledge of Nahwu included the religious factor, which is the error of reading the Quran after the spread of Islam, and the factor of Arab nationalism (qawmiyyah 'arabiyyah), that is, the desire of the Arabs to maintain the authenticity of their language. So there appeared the two most important mazhab in the history of Nahu science, that is, Basrah and Kufah. The research method applied is a comparative approach using data from literary studies related to mazhab nahwu. This research is reviewed from sociolinguistic theory, where language is part of culture In interpreting the rules of nahwu, both mazhabs make valuable contributions to Arab linguistics. This research is expected to provide a comprehensive understanding of the divergence of nahwu mazhab perspectives and encourage further exploration in the evolution of nahwu science.